STATE-OF-THE-ART: A SYSTEMATIC REVIEW OF THE LITERATURE ON FINANCIAL WELL-BEING - Kreutz, Rafael Rudolfo; Silva, Wesley Vieira da; Vieira, Kelmara Mendes; Dutra, Vanessa Rabelo (Revista Universo Contábil, 2021)
This paper aims at presenting a systematic review of the literature based on the state of the art of research on financial well-being. We systematized a research protocol based on the works developed by Tranfield, Denyer, and Smart (2003), Kitchenham (2004), and Zupic and ÄŒater (2015), to contribute to scientific knowledge about financial well-being, consistent with the methodological rigor required in RSL, which resulted in the composition of the research corpus. We search on the Scopus and Web of Science databases. The analysis includes all international publications between 1960 and 2018, comprising a total of 78 articles. Our results show that the financial well-being (demographic and socioeconomic variables, such as sex, ethnicity, age, income, education, and marital status), in addition to behavioral factors Â (attitude towards debt and financial literacy), may be indicative of theoretical gaps. We also evidenced that researchers have expended efforts on research involving the decision-making process in finance as a factor influenced by the satisfaction of people’s lives.